2021
DOI: 10.1021/acsestwater.1c00048
|View full text |Cite
|
Sign up to set email alerts
|

Visible Light-Induced Marine Bacterial Inactivation in Seawater by an In Situ Photo-Fenton System without Additional Oxidants: Implications for Ballast Water Sterilization

Abstract: Harmful non-indigenous microorganism invasion caused by ballast water discharge poses severe threats to marine environments. In this study, a conceptual in situ photo-Fenton system without additional oxidants was first established for ballast water sterilization. Pyromellitic acid diimine (PDI)-modified g-C3N4 was utilized as a photocatalyst to produce H2O2, which was in situ activated by Fe­(II) to produce •OH for deep oxidation. Marine bacterium Vibrio alginolyticus (7 log) in ballast seawater was totally in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(24 citation statements)
references
References 61 publications
0
24
0
Order By: Relevance
“…Hydrogen peroxide (H 2 O 2 ), as a green and highly efficient oxidant used in advanced oxidation processes (AOPs), is commonly produced by an anthraquinone method, an electrochemical method, and photocatalysis. Electro-Fenton (EF) is a new type of AOP, which can generate H 2 O 2 in situ on the surface of the cathode through a two-electron oxygen reduction reaction (ORR) (eq ), avoiding the risk of reagents in transportation, storage, or treatment. , The basic principle of this process is that Fe 2+ added to the solution reacts with the continuously produced H 2 O 2 to form a strong oxidant of hydroxyl radical ( • OH) (eq ); thus, it is efficient and environmentally friendly. However, traditional homogeneous EF has disadvantages such as a narrow pH application range (2.8–3.5), a slow rate of reduction of iron ions, and difficult recovery of the catalyst, which greatly limit its wide application …”
Section: Introductionmentioning
confidence: 99%
“…Hydrogen peroxide (H 2 O 2 ), as a green and highly efficient oxidant used in advanced oxidation processes (AOPs), is commonly produced by an anthraquinone method, an electrochemical method, and photocatalysis. Electro-Fenton (EF) is a new type of AOP, which can generate H 2 O 2 in situ on the surface of the cathode through a two-electron oxygen reduction reaction (ORR) (eq ), avoiding the risk of reagents in transportation, storage, or treatment. , The basic principle of this process is that Fe 2+ added to the solution reacts with the continuously produced H 2 O 2 to form a strong oxidant of hydroxyl radical ( • OH) (eq ); thus, it is efficient and environmentally friendly. However, traditional homogeneous EF has disadvantages such as a narrow pH application range (2.8–3.5), a slow rate of reduction of iron ions, and difficult recovery of the catalyst, which greatly limit its wide application …”
Section: Introductionmentioning
confidence: 99%
“…To further estimate the conduction band (CB) and valence band (VB) position of C 5 N 2 , we recorded and compared XPS VB scans of C 5 N 2 and g‐C 3 N 4 (Figure S7) and the flat band potential ( E fb ) of g‐C 3 N 4 (Figure S8) [25] . Interestingly, a significant downshift of the CB and VB position of C 5 N 2 with respect to conventional g‐C 3 N 4 and other metal‐free polymers was observed (Figure 2d and Figure S9) [2a,c,d, 10, 11, 12b, 13, 14, 23] . The CB position of C 5 N 2 was even significantly lower than 0 V vs. NHE, which was in favor of driving highly selective O 2 reduction in thermodynamics instead of competitive HER; meanwhile the lower CB would enhance WOR kinetics.…”
Section: Resultsmentioning
confidence: 94%
“…c) Experimental and Pawley‐refined PXRD patterns of C 5 N 2 . d) CB/VB position of C 5 N 2 and other reported metal‐free photocatalysts [2a,c,d, 10, 11, 12b, 13, 14, 23] . e,f) Simulated HOMO–LUMO electronic structure distribution of g‐C 3 N 4 (e) and C 5 N 2 (f) by DFT calculations.…”
Section: Resultsmentioning
confidence: 99%
“…Two electrons and two protons are consumed simultaneously to generate H 2 O 2 . This reaction pathway has now been found in various photocatalysts. g -C 3 N 4 is the first polymer photocatalyst to exhibit high selectivity (90%) toward photocatalytic H 2 O 2 production via the direct two-electron ORR pathway (Figure a) . Based on Raman and electron spin resonance (ESR) spectroscopic characterizations, it was shown that the high H 2 O 2 selectivity was attributed to the formation of 1,4-endoperoxide species on the heptazine structure (Figure b).…”
Section: Reaction Pathways Toward Overall Photosynthesis Of Hydrogen ...mentioning
confidence: 85%